STUDENTS’ PREFERRED REWARDS ON TASK ACCOMPLISHMENT - Sinta Dewi (Institut Pendidikan Indonesia Garut, 2023)
This study aims to figure out students’ preference of rewards after the accomplishment of the task given. Understanding the reasons for choosing the preferred reward also becomes the focus of the study. Descriptive study design was chosen to get the depth of understanding about the investigated issue. Semi-structured interview were questioned to 5 senior high school students in attempt to figure out their preferences of teachers rewards. The data were summarized and analyzed descriptively. The findings indicated that students preferred verbal rewards to tangible ones. The reasons for choosing the preferred reward were mostly based on the meaningfulness of the reward itself as well as its influence on their learning and psychological aspects. The study concluded that all factors that can enhance the effectiveness of reward need to be explored and understood. Keywords: Extrinsic reinforcement, reward